2017
DOI: 10.1055/s-0037-1607061
|View full text |Cite
|
Sign up to set email alerts
|

Duhamel and Transanal Endorectal Pull-throughs for Hirschsprung' Disease: A Systematic Review and Meta-analysis

Abstract: The Duhamel pull-through seems to be associated with lower incidence of anastomotic stricture compared with TEPT. The effects of the two analyzed operative techniques on constipation and enterocolitis remain unclear. The quality of evidence supporting the above findings is suboptimal, indicating the need for prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 28 publications
0
8
2
Order By: Relevance
“…The incidence of HAEC following pull-through procedures shows wide variation across studies, primarily due to varied de nitions of HAEC. Almost all comparative analyses show no signi cant difference in HAEC rates between Duhamel and TERP procedures [7,14]. In our study, pre-operative HAEC was observed in 7% of the MDPT group and 3.1% in the TERP group.…”
Section: Haeccontrasting
confidence: 45%
See 2 more Smart Citations
“…The incidence of HAEC following pull-through procedures shows wide variation across studies, primarily due to varied de nitions of HAEC. Almost all comparative analyses show no signi cant difference in HAEC rates between Duhamel and TERP procedures [7,14]. In our study, pre-operative HAEC was observed in 7% of the MDPT group and 3.1% in the TERP group.…”
Section: Haeccontrasting
confidence: 45%
“…The incidence of constipation was 30.1% in the MDPT group and 26.9% in the TERP group. Many studies have reported lower rates of constipation following TERP [13,14]. A similar constipation rate of 30% has been described following the Duhamel procedure in a follow-up among adults [18].…”
Section: Bowel Functionmentioning
confidence: 62%
See 1 more Smart Citation
“…In multivariate analyses, the following covariates were included: length of aganglionosis (short vs long segment disease, in which long segment disease was defined as aganglionosis, extending proximal to the sigmoid including total colonic aganglionosis), operation technique (for each operation technique that was observed at least 10 times in our sample), and the presence of a temporary stoma. This variable selection was based on prior evidence that suggests differences in functional outcome between patients with rectosigmoid disease compared with long-segment disease, and studies suggesting differences in surgical and functional outcome after various operation techniques (27,28). A sensitivity analysis on the relation between age at surgery and the risk of a permanent stoma was separately done in patients without intellectual disability, to assess the bias of patients who received a permanent stoma because of intellectual disability, who may have limited possibilities for bowel management with irrigations.…”
Section: Methodsmentioning
confidence: 99%
“…32,[40][41][42][43][44][45][46][47] Outcomes after Hirschsprungs PT may depend on surgical and pathological expertise, as well as perioperative care, and therefore, may be related to surgeon or hospital experience. [48][49][50] We aimed to determine whether surgeon or hospital-level HD operative volumes are associated with surgical outcomes following pullthrough in infants with HD.…”
Section: Introductionmentioning
confidence: 99%